2017
DOI: 10.5194/amt-10-459-2017
|View full text |Cite
|
Sign up to set email alerts
|

HoloGondel: in situ cloud observations on a cable car in the Swiss Alps using a holographic imager

Abstract: Abstract. In situ observations of cloud properties in complex alpine terrain where research aircraft cannot sample are commonly conducted at mountain-top research stations and limited to single-point measurements. The HoloGondel platform overcomes this limitation by using a cable car to obtain vertical profiles of the microphysical and meteorological cloud parameters. The main component of the HoloGondel platform is the HOLographic Imager for Microscopic Objects (HOLIMO 3G), which uses digital in-line holograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 50 publications
1
62
0
Order By: Relevance
“…A random forest model (Breiman, 1996(Breiman, , 2001 constitutes an ensemble of decision trees that are combined through averaging over multiple individual trees. Decision tree approaches have previously been used for cloud particle classification specifically (e.g., Garimella et al, 2016;Bernauer et al, 2016) and are frequently used for any classification prob-lems, such as data from single particle mass spectrometry (e.g., Christopoulos et al, 2018). Ruske et al (2018) recently identified best performance of random forest models when comparing different ML approaches to classify different particle types.…”
Section: Particle Shape Classification: Supervised Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…A random forest model (Breiman, 1996(Breiman, , 2001 constitutes an ensemble of decision trees that are combined through averaging over multiple individual trees. Decision tree approaches have previously been used for cloud particle classification specifically (e.g., Garimella et al, 2016;Bernauer et al, 2016) and are frequently used for any classification prob-lems, such as data from single particle mass spectrometry (e.g., Christopoulos et al, 2018). Ruske et al (2018) recently identified best performance of random forest models when comparing different ML approaches to classify different particle types.…”
Section: Particle Shape Classification: Supervised Machine Learningmentioning
confidence: 99%
“…A major limitation of these devices is the low frame rate on the order of a few tens of particles per second, which limits the number of single particles sampled. This becomes problematic when hydrometeors of different phase are inhomogeneously spatially distributed within clouds (Korolev and Isaac, 2006;Beck et al, 2017). Besides, high frame rates are beneficial for laboratory studies, where particle number concentration easily exceeds a few tens of particles per cubic centimeter, and low frame rates lead to coincidence errors even at moderate number concentrations (Cotton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Siebert et al 2006), cable cars (e.g. Beck et al 2017), tethered balloon systems (TBS) (e.g. Siebert et al 2003, Maletto et al 2003, Lawson et al 2011, Sikand et al 2013, Canut et al 2016 or launched balloon platforms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud particle imaging probes (e.g. CPI (Lawson et al, 2001), CIP (Baumgardner et al, 2001) and PHIPS-HALO (Abdelmonem et al, 2011) directly capture a 2D particle image of single cloud particles, whereas digital in-line holography (e.g., HOLODEC, , HOLIMO 2, Henneberger et al (2013), HOLIMO 3G, Beck et al (2017) and…”
mentioning
confidence: 99%
“…Particles between the lens and the camera scatter the light which interferes with the plane reference wave. The interference pattern is captured by the camera as a hologram from which images in different distances to the camera can be reconstructed.Figure adaptedfromBeck et al (2017).…”
mentioning
confidence: 99%